2011
DOI: 10.1159/000334064
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the Myriad Genomics of Complex Disorders, Specifically Focusing on Autism, Epilepsy, and Schizophrenia

Abstract: Analyses of structural genome variation by array-CGH have dramatically enhanced our ability to detect copy number variations (CNVs). De novo CNVs and those co-segregating with disease in a family are generally interpreted as pathogenic. Yet, often CNVs, such as recurrent microdeletions in region 15q13.3, are not so clearly pathogenic. Here we discuss potential confounding mechanisms that may lead to the phenotypic pleiotropy of CNVs, such as unmasking of recessive alleles by hemizygous deletions, interaction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
76
1
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(82 citation statements)
references
References 218 publications
(114 reference statements)
4
76
1
1
Order By: Relevance
“…30,32,34,38 Our results are consistent with this observation as patients 3 and 4 with duplication of exon 5 have ASDs. Both these duplications are not expected to alter the reading frame, but can result in addition of amino-acid residues to the amino terminus of the protein.…”
Section: Discussionsupporting
confidence: 90%
“…30,32,34,38 Our results are consistent with this observation as patients 3 and 4 with duplication of exon 5 have ASDs. Both these duplications are not expected to alter the reading frame, but can result in addition of amino-acid residues to the amino terminus of the protein.…”
Section: Discussionsupporting
confidence: 90%
“…The results of such studies will also present us with novel challenges during genetic counselling of families. [58][59][60][61][62][63] In conclusion, this study suggests that CNVs may contribute to clinical phenotypes by a recessive mode of gene action. We conclude that array-based enrichment of inherited deletions may be a targeted and highly sensitive method to detect SNVs and CNVs, simultaneously.…”
Section: Discovery Of Variants Vs Hemizygous Deletions R Hochstenbachmentioning
confidence: 55%
“…When CNVs are found that may explain the epilepsy, monogenic causes can easily be overlooked. 20 We found three regions with overlapping CNVs in more than one patient, at 16p13.11, 7q36.3, and 9p23. The CNVs at 16p13.11 further limit the epilepsy candidate genes in this region to ABCC1 and ABCC6.…”
Section: Discussionmentioning
confidence: 68%